The Impact of Terrorism And Political Events On Stock Market: Empirical Evidence From Pakistan - Iqbal, 4 Imran Hussain Shah, 1Khakan Najaf, 2Rabia Najaf, 3Amir (International Journal of Scientific Research and Management (IJSRM), 2016)
The aim of this paper is to explore the relationship between political & terrorist activities in Pakistan on thestock market development. The paper presents data on the reaction of financial markets to the terrorist attacks andpolitical instability in Pakistan (2011-2014). T-statistic is used to measure the impact of terrorism and politicalevents on stock exchange market. In order to determine the Average return (AR), moving average method isused .The results of the study have shown that Terrorism and Political events negatively affect stock market returnsin the short run; whereas there is no significant relationship between stock market returns, Terrorism and Politicalevents in the long run. A potential limitation of the study was the constraint related to the available yearlyeconomic growth and other economic variables' data. The data for the study was based on the terrorist & politicalactivities for the year 2010 to 2014 on an incident to incident basis. Based on the empirical results, it is beingrecommended that governments should pay particular attention to economic recovery in the aftermath ofterrorist attacks and political unrest and the policies aimed at combating terrorism must be the priority of thegovernment, so that its harm can be reduced, if not exterminated. Political unrest can be addressed throughparliament house and judiciary. Terrorism and Political events, with its all kinds of impacts, affect the society and itsactivities and therefore must be eliminated if an economy needs to prosper. This study envisions the overall impactof terrorist activities and political events, not just as a single activity but also on the health of the economy. Forstudying this impact, a t-statistics has been used for this study